A new neornithischian dinosaur from the Upper Jurassic Tiaojishan Formation of northern China - Yang, Yunfeng; King, James L.; Xu, Xing (PeerJ, 2025)
The Middle and Late Jurassic Yanliao Biota is different from other contemporaneous fossil assemblages in that it lacks neornithischian dinosaurs. Here, we report a new, early-diverging neornithischian, Pulaosaurus qinglong gen. et sp. nov., from the Upper Jurassic Tiaojishan Formation of Qinglong, Hebei Province, of northern China. Diagnostic or noteworthy morphological characteristics of P. qinglong include: five premaxillary teeth; a small boss is present on the caudoventral corner of the dorsal ramus of the jugal; a nuchal crest is located along the parietal; the manus has five digits; a supra-acetabular crest is present on the ilium; the paired arytenoids are gracile and leaf-like in form; the obturator process along the ischium is located near the pubic peduncle; a notch-like shaped obturator opening is present within the pubis; a robust fibular condyle forms a dorsoventrally extending crest on the tibia; a subtriangular flange on the anterior surface of the astragalus extends dorsolaterally along three distal tarsals; three of the distal tarsals are unfused, including a small drop-shaped distal tarsal 3; distal tarsal 3 is pierced by a foramen. A phylogenetic analysis places P. qinglong as one of the earliest-diverging neornithischians yet described. Moreover, P. qinglong represents the second known dinosaur to preserve ossified laryngeal elements, thus suggesting that a bird-like vocalization evolved early in non-avian dinosaur evolution.
Keywords: Yanliao biota; Neornithischia; Laryngeal elements